Numerical solution to flow of Casson fluid via stretched permeable wedge with chemical reaction and mass transfer effects - Hussain, Majid; Shoaib, Muhammad; Ranjha, Qasim A.; Anwar, Muhammad Shoaib; Ahmad, Zahoor; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
The purpose of this research is to discuss a two-dimensional (2D), laminar, continuous flow of Casson liquid through a stretched porous wedge in the presence of chemical reaction and buoyancy effects over wedge. This research is aimed at analyzing chemically reacting flow of Casson model over a heated porous wedge in order to understand the features of dynamic wedge. The governing equations and involved parameters are nondimensionalized using transformations. Bvp4c, a numerical tool in Matlab is employed to assess the solution. Significant findings of the major dimensionless parameters on state profiles of velocity, temperature and concentration are drawn graphically. The principal results indicate the impacts of Casson parameter, Eckert and Prandtl number, R stretching parameter, K1 chemical parameter, Sc Schmidt number, C mass transfer parameter, m wedge angle parameter on concentration, velocity and temperature field. The Sherwood, Nusselt number and skin friction numerical values are presented in tabular form. Major findings show that drag force at wedge declines for greater K1. Nusselt number shrinks for larger behavior for K1. Sherwood number upsurges for greater performance for chemical reaction parameter K1. Moreover, K1 upsurges the temperature slowly but the impacts of K1 on concentration show a decreasing behavior.
Keywords: Fluid mechanics; chemical reaction; stretching wedge flow; numerical solution; buoyancy effects